Cryptogenic stroke in young patients and cannabis use: case presentation and literature review - Atkočiūnas , A.; Jasionis , A.; Lengvenis , G.; Badaras , R.; Ryliškienė , K. (Neurologijos seminarai, 2019)
Approximately 10% of ischemic strokes occur in people under the age of 50 – this is called early on set or stroke in young adults. In this patient population, there is an especially high number of cryptogenic strokes, where etiology is not identified or several causes are identified, or their exact meaning is not entirely clear, e. g., patent foramen ovale. One of the possible explanations of the increasing incidence in early onset stroke includes an increasing use of psychoactive substances. Most commonly used psychoactive substance in the world and in Lithuania is cannabis; the consumption of synthetic cannabinoids (spice), which is often considered as harmless in society, is also growing. The first case of focal neurological deficiency associated with cannabis use was published five decades ago. There is a number of hypotheses explaining the effect of cannabis and synthetic cannabinoids use on the etiology of stroke, but their proof is difficult. In this article we present a case of cryptogenic stroke in a young patient and review literature on the relationship between the use of cannabis and synthetic cannabinoids and stroke.